Politics and Prosperity in a Religious-Political Nigerian Society: Reflection of a Christian Theologian - Mishi, Silas Guda; Ikyernum, Ephraim S. (Kashere Journal of Politics and International Relations, 2023)
Politics is a medium through which the society seeks to be organized and governed in order to improve human potentials, social relations and economic viability for the overall benefit and prosperity of the members and society. This entails that one major hallmark or aim of politics is to drive the society and members towards prosperity, and prosperity is multidimensional – it stretches to include good social relations and economic wellbeing. Good social relationship is built on the pillars of righteousness or moral uprightness, equity and justice. It is not surprising that there is a nexus between religion and politics, and the religions (Islam, Christianity and African Traditional Religion) uphold these tenets as the ideals of good interpersonal dealings and relationship among members of the society. It is however, observed that the understanding and concept of prosperity among political players in Nigeria today is skewed and lopsided. It is based mainly on selfish interests and economic prosperity and material wellbeing, almost or totally neglecting the other important aspects of prosperity. This paper therefore, seeks to re-echo what better, and or true politics is, and the fact that prosperity is multidimensional, with emphasis from the religious perspective. Allusion may be made to Islam and the African Traditional Religion, but focus is mainly on the Tanakh – the Old Testament part of the Christian scriptures as well as other relevant parts of the Christian canon – Bible. This research work is built on Justin Ukpong's Enculturation hermeneutics (also called enculturation hermeneutics) hermeneutical theory and reconstruction hermeneutics.